Anti-Acetylcholinesterase, Anti-Inflammatory and Anti-Oxidant Activities of Raw-Extract Centella Asiatica (RECA) on Lipopolysaccharide (LPS)-Induced Neuroinflammation Sprague Dawley Rats - Hafiz, Z; Shamsuddin, N; M Mukhtar, S; J James, R; I Adenan, M (International Journal of Engineering and Technology, 2019)
The present study was designed to investigate the potential of raw-extract of Centella asiatica (RECA) in suppressing acetylcholinesterase (AChE), inflammations and oxidative stress via induction of lipopolysaccharide (LPS) on animal model of Sprague Dawley rats. Centella asiatica is a plant thatÂ has been used as a traditional herbal remedy for the management of several diseases, including memory improvement, treatment of mental fatigue and wound healing. Pre-treatment with RECA in vitro significantly reduced the AChE activity in a concentration-dependent manner with IC50 value of 57.47 Â± 13.55 Âµg/ml. Interestingly, this result was parallel with in vivo studies. Moreover, the level of pro-inflammatory cytokines and oxidative stress were significantly reduced by RECA in dose-dependent manner. Overall, our findings clearly dictate the potential of RECA as AChE inhibitor as well anti-inflammatory and anti-oxidant agents.Â